Evaluation of sit-stand workstations in an office setting: a randomised controlled trial. (December 2015) - Graves, Lee; Murphy, Rebecca; Shepherd, Sam; Cabot, Josephine; Hopkins, Nicola
Abstract Background Excessive sitting time is a risk factor for cardiovascular disease mortality and morbidity independent of physical activity. This aim of this study was to evaluate the impact of a sit-stand workstation on sitting time, and vascular, metabolic and musculoskeletal outcomes in office workers, and to investigate workstation acceptability and feasibility. Methods A two-arm, parallel-group, individually randomised controlled trial was conducted in one organisation. Participants were asymptomatic full-time office workers aged ≥18 years. Each participant in the intervention arm had a sit-stand workstation installed on their workplace desk for 8 weeks. Participants in the control arm received no intervention. The primary outcome was workplace sitting time, assessed at 0, 4 and 8 weeks by an ecological momentary assessment diary. Secondary behavioural, cardiometabolic and musculoskeletal outcomes were assessed. Acceptability and feasibility were assessed via questionnaire and interview. ANCOVA and magnitude-based inferences examined intervention effects relative to controls at 4 and 8 weeks. Participants and researchers were not blind to group allocation. Results Forty-seven participants were randomised (interventionn  = 26; controln =  21). Relative to the control group at 8 weeks, the intervention group had a beneficial decrease in sitting time (−80.2 min/8-h workday (95 % CI = −129.0, −31.4);p  = 0.002), increase in standing time (72.9 min/8-h workday (21.2, 124.6);p  = 0.007) and decrease in total cholesterol (−0.40 mmol/L  (−0.79,  −0.003);p  = 0.049). No harmful changes in musculoskeletal discomfort/pain were observed relative to controls, and beneficial changes in flow-mediated dilation and diastolic blood pressure were observed. Most participants self-reported that the workstation was easy to use and their work-related productivity did not decrease when using the device. Factors that negatively influenced workstation use were workstation design, the social environment, work tasks and habits. Conclusion Short-term use of a feasible sit-stand workstation reduced daily sitting time and led to beneficial improvements in cardiometabolic risk parameters in asymptomatic office workers. These findings imply that if the observed use of the sit-stand workstations continued over a longer duration, sit-stand workstations may have important ramifications for the prevention and reduction of cardiometabolic risk in a large proportion of the working population. Trial registration ClinicalTrials.govNCT02496507 .